Recent advances on nano-adsorbents and nanomembranes for the remediation of water. (1st November 2021) - Puri, Nidhi; Gupta, Anjali; Mishra, Anuradha
Abstract: Water is the most essential thing to life on earth but in water scarce regions of the world do not have easy access to clean water for their daily needs. One of the major causes of clean water accessibility to all is the contamination of various pollutants in water bodies. The common water pollutants are inorganic heavy metal ions, organic impurities, and microorganisms. To overcome this problem, a large number of water remediation techniques have been in use since ancient times. In the last four decades, there are breakthrough developments in the methods for water purification and the most important one is the use of nanoscale materials. The application of engineered nanoparticles and nanomembranes are the most recent ones. This review article has incorporated the recent advances in water purification methods using engineered nanoparticles and nanomembranes. The risk associated with use of nanoscale materials and the future aspects have also been highlighted in the article. Graphical abstract: Image 1 Highlights: Advanced nanoscale materials are used for the water remediation process. Nano-adsorbents work well in water process via chemical and physical interactions. Nanomembranes are selective and reusable filtration membranes for water process. Metal-organic frameworks are new and effective nano-adsorbents for water treatment.